Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1016/s0029-7844(97)00665-0
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable Response of Primary Squamous Cell Carcinoma of the Ovary to Paclitaxel and Cisplatin

Abstract: Paclitaxel and cisplatin may be effective in treating primary squamous cell carcinoma of the ovary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 6 publications
0
24
0
Order By: Relevance
“…Neither the CA19-9 marker nor erythrocyte sedimentation rate was analyzed in the other reported cases. Determination of CEA was also interesting; however, it was measured only by Eltabbakh et al [16] and found to be increased in that stage IV case, as in the patient that we studied. In the latter, it was highly probable that CEA was secondary to the infiltration and severe intestinal involvement.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Neither the CA19-9 marker nor erythrocyte sedimentation rate was analyzed in the other reported cases. Determination of CEA was also interesting; however, it was measured only by Eltabbakh et al [16] and found to be increased in that stage IV case, as in the patient that we studied. In the latter, it was highly probable that CEA was secondary to the infiltration and severe intestinal involvement.…”
Section: Discussionmentioning
confidence: 58%
“…The patients with SCC associated with endometriosis had a poorer overall survival than did those with SCC associated with a dermoid cyst (1 of 6 versus 12 of 18, respectively), and survival was also related to the stage of the tumor and its grade of differentiation. Only 3 patients were alive when the case was published: case 7 from Pins et al [4], case 14 from Eltabbakh et al [16], and case 16 from Mhawech et al [18]; 2 cases were at stage I (cases 7 and 16). Other endometriosis-related malignancies, especially endometrioid and clear cell carcinomas, have a favorable prognosis (70.4% of cases without recurrence in the series of Leiserowitz et al [6] with a mean follow-up of 31 months), with a better response to postoperative chemotherapy and radiation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Eltabbakh et al [9] first reported the efficacy of monthly paclitaxel-cisplatin chemotherapy in a patient with stage IV ovarian SCCE that had metastasized to the liver. Their patient showed a remarkable response following treatment of the residual tumor in the liver with six courses of monthly paclitaxel-carboplatin administration and survived for 2 years after the initial diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our postsurgical first-line chemotherapic regimen consisted of the administration of six courses of paclitaxelcarboplatin on a tri-weekly basis-after informed written consent was obtained from the patient. Our decision to use paclitaxel and carboplatin was based on excellent results reported for that combination in treating ovarian SCCE [9,10]. This treatment was effective during the first six courses of paclitaxel-carboplatin as the SCC level was maintained at \0.5 ng/mL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation